Simulation of beam extraction and space charge effect in an electromagnetic isotope separator. (November 2022) - Liu, Y.G.; Huang, W.; Wu, Q.; Liu, J.L.; Zhang, X.; Zhou, Y.; Zhai, Y.J.; Sun, L.T.
Abstract: Space charge effect of intense ion beam has critical influence on separation efficiency in the electromagnetic isotope separator. In this paper, a ribbon beam extraction system with slit electrodes for an electromagnetic isotope separator was designed and studied. The extracted beam currents were varied from 10 to 40 mA and the corresponding extracted beam energies were 40 keV and 100 keV respectively. The simulated output beam density distributions were used in the subsequent multi species particle transmission simulation with the space charge effect included. The separated isotope beam spot distributions at the focal plane were simulated under different space charge compensation factors and thus the optimum operation gas pressures in vacuum box were roughly estimated. For the case of high intensity and high power isotope beam collection, an isotope collector with a deceleration electrode was proposed to mitigate the effect of high power beam bombardment and the resultant temperature rising on the collector surface. Highlights: The ribbon beam extraction systems were simulated for an electromagnetic isotope separator. The influence of space charge effect on isotopes separation efficiency was studied via numerical simulations. The optimal residual gas pressure for fully beam space charge neutralization was roughly estimated.